ANALISIS PENERAPAN GRI STANDARS 404, BIAYA RATA-RATA PELATIHAN DAN RASIO PENGELUARAN BIAYA KUALITAS PELATIHAN DAN PENDIDIKAN TERHADAP TOTAL BIAYA OPERASIONAL LAINNYA PADA BANK BUMN - Lin Oktris; Kiki Kusumayadi Ahadiyat (Universitas Agung Podomoro, 2022)
This study conducted to analize the application of GRI Standards 404 on Government Owned Banks in Indonesia (Bank Mandiri, BRI, BNI and BTN), the avarage training and educational cost for employee, and the ratio of total training and educational cost (as a part of quality cost) to total other operating cost in each Government Owned Banks. The data used are secondary data, obtained from official website of each banks. Sustainability Reporting and Financial Report for the year of 2020 are the basic data used for this study. This study is a case study. This study shows that all of Government Owned Banks are conforms to GRI Standards 404 about employee’s training and education. They are spending a substantial amount of training and education cost on 2020, but the ratio of training and education cost to total other operating cost are unsubtantial.